2004
DOI: 10.1161/01.str.0000141415.28155.46
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Linkage in a Large Dutch Consanguineous Family Maps a Locus for Intracranial Aneurysms to Chromosome 2p13

Abstract: Background and Purpose-Familial occurrence of intracranial aneurysms suggests a genetic factor in the development of these aneurysms. In this study, we present the identification of a susceptibility locus for the development of intracranial aneurysms detected by a genome-wide linkage approach in a large consanguineous pedigree. Methods-Patients with clinical signs and symptoms of intracranial aneurysms, confirmed by radiological, surgical, or postmortem investigations, were included in the study. Magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…All computations were performed using the HEGESMA_v2.0 software available online at http://biomath.med.uth.gr. Two large Japanese studies [8,10] were included in a sensitivity analysis, excluding the three Caucasian studies [6,7,9] with the highest maximum log of the odds ratio (LOD) reported, which were also the three smallest studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All computations were performed using the HEGESMA_v2.0 software available online at http://biomath.med.uth.gr. Two large Japanese studies [8,10] were included in a sensitivity analysis, excluding the three Caucasian studies [6,7,9] with the highest maximum log of the odds ratio (LOD) reported, which were also the three smallest studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hand searching of reference lists of identified articles was also carried out. We identified eight whole-genome scans between the years 2001 and 2007 [3][4][5][6][7][8][9][10]. Studies included in our analysis all assessed the linkage of autosomal genome sites with familial intracranial aneurysm.…”
Section: Selection Of Genome Scans and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations